PJMHS 2022
DOI: 10.53350/pjmhs20221611484
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Expulsion of Lower Ureteric Stones in Patients with Elevated Level of C-Reactive Protein

Abstract: Background: Around 4–15% of people worldwide have urolithiasis, and ureteric stones account for around 20% of this condition. One of the most frequent situations a urologist has to deal with is acute renal colic caused by urolithiasis. Objective: To determine the spontaneous expulsion of lower ureteric stones in patients with elevated level of c-reactive protein Methodology: This descriptive cross sectional study was performed at the urology department Khalifa Gul Nawaz Teaching Hospital, Bannu Medical College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Age distribution revealed that the majority of patients were within the 31-40 age groups, with other age groups having varying representation. Similarly, Hamid et al [25] categorised the patients based on age distribution, revealing that 45.7% belonged to the 18-30-year age group, another 45.7% were from the 31-45-year age group, and the remaining 18.7% were aged 46-60 years. In another study, 44.9% belonged to the 18-30-year age group, 46.4% to the 31-45-year age group, and the remaining 18.7% were aged 46-60 years [26].…”
Section: Discussionmentioning
confidence: 99%
“…Age distribution revealed that the majority of patients were within the 31-40 age groups, with other age groups having varying representation. Similarly, Hamid et al [25] categorised the patients based on age distribution, revealing that 45.7% belonged to the 18-30-year age group, another 45.7% were from the 31-45-year age group, and the remaining 18.7% were aged 46-60 years. In another study, 44.9% belonged to the 18-30-year age group, 46.4% to the 31-45-year age group, and the remaining 18.7% were aged 46-60 years [26].…”
Section: Discussionmentioning
confidence: 99%